Rationalization of the Use of Alternative Rolling Stock for Transportation of Vegetable Cargo with Insufficient Number of Grain Hoppers - Lavrukhin, O; Zapara, V; Baulina, H; Zapara, Y; Kyman, A (International Journal of Engineering and Technology, 2018)
The main problems of transportation of vegetable cargo by the Ukraine railway transport are considered. It was established that as grain export grows rapidly and subject to the current technical condition of the railway, the number of special rolling stock â€“ grain hoppers â€“ is insufficient. The article proposes using an alternative rolling stock â€“ a covered car. The use of metal door panels in the car has been proposed to ensure the car loading without restrictions on the height of loading in the doorway space and the complete safety of the cargo with the increased use of the load capacity of covered cars. The influence of loading density of the loaded cargo on the degree of use of loading capacity and loading volume of the car was investigated when standard wooden door panels are used vs. proposed metal door panels. The study have proved significant economy of the covered car fleet during transportation of vegetable cargo with the use of metal door panels in the loading density range of the cargo from a minimum to 610 kg/m3.Â Â